Tourism Employment And Marketing In Paradise-Bali (Editorial) - Subadra, I Nengah (Language Assistance, 2023)
The Bali Journal of Hospitality, Tourism and Culture Research features articles on tourism employment and marketing research in this volume. The journal aims to present a range of insightful articles that explore the intersection of tourism, employment, and marketing. As the global tourism industry continues to evolve and expand, it is imperative to examine the intricate relationship between tourism activities and their impact on employment and marketing dynamics (Subadra, 2019) It shifts the focus towards the contemporary landscape of tourism employment investigating the influence of technological advancements, changing consumer behaviours, and sustainability considerations. This section aims to explain the changing nature of tourism-related jobs, including the emergence of new roles, in-demand skills, and the impact of digitalization on employment patterns within the tourism sector. It also covers marketing topics related to consumer behaviour, satisfaction, loyalty, and digital marketing.